Compliance Intention of Prospective Taxpayer in Indonesian based on Nationalism and Tax Sanctions - Wardani, Dewi Kusuma; Astuti, Aprilia Dewi (Universitas Muhammadiyah Surakarta, 2023)
The phenomenon of the Covid-19 pandemic disrupted the economy in Indonesia, including from the tax sector. Tax is the biggest source of revenue for a country in Indonesia. The success of implementing taxation in Indonesia is determined by the domination of taxpayer compliance. This study adopts the theory of planned behavior (TPB) which aims to determine the effect of nationalism and tax sanctions on the compliance intention of prospective taxpayers. The method used in this research is descriptive statistics with convenience sampling technique. The population of this study is prospective taxpayers aged 14-22 years with a total sample of 204 people. Samples were taken from students in Indonesia. The results of the study show evidence of a positive influence of nationalism on tax compliance. Tax sanctions have no effect on the intention to comply with prospective taxpayers. This study expands the theoretical knowledge framework by studying and researching the factors that contribute significantly to the taxation sector in Indonesia as an effort to economic development in Indonesia through taxes.